STEM-Integrated Flipped Classroom in the Teacher’s Perspective: Could its Implementation in E-Module Improve System Thinking Ability? - Aspridanel, Almira; Abdurrahman, Abdurrahman; Lengkana, Dewi; Jalmo, Tri (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study aims to describe the teacher’s perception of flipped classroom learning strategy using STEM-integrated E-Modules in improving systems thinking ability. The research was conducted in Lampung Province, Indonesia, and was nvolving 50 junior high school science teachers. The method used in this research is mixed methods with Sequential Explanatory Design. Data was retrieved using Questionnaire, and were analyzed using descriptive analysis. The survey results show that teachers have a positive perception of the STEM approach. The results of the analysis also show that most teachers have not used the STEM approach in schools to provide an understanding of science. In addition, teachers also have not implemented STEM-integrated teaching materials.